HUBUNGAN JENIS KELAMIN, INDEKS MASSA TUBUH DAN PERAWATAN WAJAH DENGAN DERAJAT KEPARAHAN ACNE VULGARIS - Gomarjoyo, Fanny; Kartini, Agnes; Nuryanto, M. Khairul (Jurnal Kebidanan Mutiara Mahakam, 2019)
Acne vulgaris is one of problem skin disease for adolescents and young adults. Acne vulgaris(AV) is a chronic inflammation of pilosebasea follicles with multifactorial causes and has clinicalmanifestations such as blackheads papules, pustules, nodules and cysts. Risk factor of acne vulgaris isobesity. Obesity usually happens along with peripheral hyperandrogen and can increase sebumproduction. Facial care consists of cleaning, moisturizer and sun protector and analyzed relation withseverity of acne vulgaris. The purpose of this study was to determine the relationship of gender, bodymass index and facial care to severity of acne vulgaris. This study was an observational analytic withcross sectional method and the sampling was chosen by purposive sampling. The minimum sample sizewas 59 subjects. Data from this study were obtained from measurement of body mass index anddiagnostic photos in acne prone subjects. The result of statistical tests showed that there was relationshipbetween sex with the severity of acne vulgaris with (p = 0.014) and severity of acne vulgaris having anopportunity 6 times greater in males than females. Body mass index and facial care have no relation tothe severity of acne vulgaris.